Enhancing the halal food industry by utilizing food wastes to produce value-added bioproducts - Sulaiman, Alawi; Othman, Nasuddin; Samsu Baharuddin, Azhari; Mokhtar, Mohd Noriznan; Tabatabaei, Meisam (Elsevier, 2014)
Each year, millions of tons of halal food wastes are being disposed into the environment through land-filling or illegal dumping activities. Currently, the government has no other cheaper and easier options than landfill. Dumping of organic waste materials into the environment will partly contribute to the global warming phenomenon due to methane gas generation through anaerobic process, occurred inside the landfill or river bed. Methane gas has 21 times higher global warming potential (GWP) than carbon dioxide and can severely affect the environment if not properly managed. Therefore this paper will highlight the concept of biorefinery to enhance the current state of halal food waste handling which include kitchen waste, waste cooking oil, food waste, landscaping and garden waste, wet market waste, night market waste, halal slaughterhouse waste, food processing facility waste and other types of halal waste. Through biorefinery complex these waste materials can be converted into value-added bioproducts such as biodiesel, biogas, bioethanol, animal feed, biofertilizer, bioplastic, biomaterial and others. This will enhance the food halal industry and also support the government aspiration towards achieving high income country.